Predictors of dietary practices and nutritional status among diabetic type II patients in Kiambu County, Kenya - Wahome, Emily M.; Makau, Wambui Kogi; Kiboi, Willy K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Diabetes type 2 has become a serious global health threat due to its increasing prevalence particularly among African countries. Numerous scientific evidence points out on the importance of an individual’s dietary practices and nutritional status in its prevention and management. The objective of the study was to identify the predictors of dietary practices and nutritional status among diabetes type 2 patients. Methods: This was a cross-sectional study and a total of 153 study subjects were recruited. A pretested researcher administered questionnaire was used to collect data. The data was analyzed using both bivariate and multivariate logistic regression. Results: The study established significant associations (p<0.05, at 95% C.I) between participants’ education level (AOR=4.72), occupation (AOR=2.41), monthly income (AOR=6.02) and level of dietary knowledge (AOR=2.33) and their dietary practices. Further, there was a significant association between nutritional status and education level (AOR=1.26), monthly income (AOR=1.72), level of dietary knowledge (AOR=1.11) and dietary diversity (AOR=1.62). Majority of the participants were obese (51%). Conclusions: Majority of the participants were obese. Dietary knowledge, education level, occupation, monthly income and dietary practices were the factors associated with the patients’ dietary practices and nutritional status. Up-scaling of interventions targeting these variables is thus crucial. Further, reinforcing the need for healthy dietary practices and optimal nutritional status is critical in the prevention and management of diabetes.